Economic Freedom Indicators and Higher Education Reforms: Evaluation and Planning Internationalization Process - Khalid Zaman; Muhammad Qaiser Saleem; Mehboob Ahmad; Aamir Khan (International Journal of Economics and Financial Issues, 2017)
This study contributes to the body of knowledge by measuring the effects of economic freedom indicators on higher education reforms in selected SAARC countries over a period of 1995-2012. The results show a strong linkage between economic freedom indicators and higher education,which support the internationalization policies of higher education institutions in the region. The results indicate that “freedom from corruption” increases higher education expenditures and literacy rate in Bangladesh, while trade freedom, financial development, property rights, and government spending have a positive impact on higher education expenditures and per capita GDP in India, Nepal, Pakistan, and Sri Lanka. Property rights increases the higher education enrollment, higher education spending per student, and R&D expenditures in Pakistan, while government spending in Sri Lanka has a positive relationship with the literacy rate and R&D expenditures.  The results of panel fixed effect regression model confirm the importance of economic freedom indicators in higher education reforms in selected SAARC countries. The study concludes that economic freedom indicators enforce the need of higher education reforms, which is prerequisite for internationalization process across the globe.